EVALUATION OF THE PARKING LOTS BY USING INTERVAL VALUED INTUITIONISTIC FUZZY PROMETHEE APPROACH: AN EXAMPLE FOR ISTANBUL - Tuzkaya, Umut Rifat; Yilmazer, Busra; Tuzkaya, Gulfem; Sennaroglu, Bahar (WORLD SCIENTIFIC PUBL CO PTE LTD, 2016)
Because of the high population density, Istanbul has the scarcity of parking spaces. With the aim of meeting the demand for car parks, authorities are planning to construct various parking lots in Istanbul. To find convenient locations and construct well designed parking lots, current ones should be evaluated. In this study, randomly chosen parking lots in Istanbul is compared according to the literature based criteria by using interval-valued intuitionistic fuzzy PROMETHEE. The main objective is determining the best ones and making a gap analysis to find the right parking lot types and convenient locations for them.
Keywords: DECISION-MAKING; Computer Science